Impact of Sensory Processing Sensitivity on Emotional Dysregulation in Gifted Students: The Mediating Role of Anxiety Sensitivity - Abedi, Ahmad; Nejatifar, Sara (Psychological Research in Individuals with Exceptional Needs, 2025)
This study aimed to investigate the impact of sensory processing sensitivity on emotional dysregulation in gifted students, examining the mediating role of anxiety sensitivity in this relationship. The research employed a descriptive correlational design, involving a sample of 390 gifted secondary school students from Isfahan city, selected based on Morgan and Krejcie’s sampling table. Participants completed three validated Likert-based instruments: the Highly Sensitive Person Scale (HSPS), the Anxiety Sensitivity Index-3 (ASI-3), and the Difficulties in Emotion Regulation Scale (DERS). Data analysis was conducted using SPSS-27 for descriptive statistics and Pearson correlation analysis, and AMOS-21 for structural equation modeling (SEM) to assess direct, indirect, and total effects among the variables. Model fit was evaluated using standard indices including RMSEA, CFI, TLI, and GFI. Pearson correlation coefficients indicated significant positive relationships between sensory processing sensitivity, anxiety sensitivity, and emotional dysregulation (r = .56 to .67, p < .001). The SEM results showed that sensory processing sensitivity had a significant direct effect on emotional dysregulation (β = .42, p < .001), and on anxiety sensitivity (β = .56, p < .001). Anxiety sensitivity also directly predicted emotional dysregulation (β = .49, p < .001). Importantly, anxiety sensitivity partially mediated the relationship between sensory processing sensitivity and emotional dysregulation, with a significant indirect effect (β = .28, p < .001). The model demonstrated excellent fit indices (CFI = .96, RMSEA = .052, χ²/df = 2.07). The findings underscore the importance of recognizing and addressing anxiety sensitivity as a key psychological mechanism linking sensory traits and emotional dysregulation in gifted youth. Interventions that integrate emotional regulation and sensitivity awareness may enhance educational and psychological outcomes for this population.